Family Caregiver Factors Associated With Emergency Department Utilization Among Community-Living Older Adults With Disabilities - Julia Burgdorf; John Mulcahy; Halima Amjad; Judith D. Kasper; Kenneth Covinsky; Jennifer L. Wolff (SAGE Publishing, 2019)
Background: Older adults with disability are frequent users of the emergency department (ED) and often rely on family caregiver support. We identify whether and which caregiver characteristics are associated with older adults' ED use. Methods: We use Cox proportional hazards regression to model the likelihood of all-cause ED use (defined as 1 or more visits within 12 months of survey) as a function of caregiver characteristics after adjusting for older adult sociodemographic and health characteristics. We draw from linked older adult and caregiver surveys and administrative claims, creating a sample of 2521 community-living older adults with mobility/self-care disability receiving care from a family or unpaid caregiver. Results: About half (52.5%) of older adults receiving mobility or self-care help incurred 1 or more ED visits within 12 months of interview. Adjusting for year of data collection, sociodemographic characteristics, and health status, these older adults were at greater risk of all-cause ED use if their primary caregiver provided greater than 40 hours of care per week (hazard ratio [HR] 1.22, 95% CI 1.04-1.43; P = .02), helped with health care tasks (HR 1.26; 95% CI 1.08-1.46; P < .01), or experienced physical strain (HR 1.18; 95% CI 1.03-1.36; P = .02). Conclusion: Caregiver strain, helping with health care tasks, and greater hours of help per week are associated with heightened risk of ED use among older adults receiving mobility or self-care help. Study findings suggest the potential benefit of caregiver assessment and support.